Seed Yield and Biological Nitrogen Fixation for Historical Soybean Genotypes - S. Tamagno; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2017)
Seed yield formation and biological nitrogen (N) fixation (BNF) were evaluated during the seed filling period (SFP) for historical soybean genotypes under contrasting N strategies. Overall, seed yield increased with the year of release, primarily associated with increments in the seed number component. The study showed that seed weight factor was maintained across decades regardless of the improvement in seed number. Nitrogen factor, evaluated as zero-N application via inorganic fertilizers versus high-N added, influenced seed yield via impacting seed weight factor. The latter plant trait improved with the high-N treatment, which was related to changes in the duration of the SFP rather than in the rate (seed biomass accumulation per day). The BNF parameter also reflected changes during the SFP related to the N treatment implemented, with high BNF (c.a. peak around 70-90%) under zero-N treatment, but still providing N via BNF at a lower rate (c.a. peak around 40-50%) for the high-N treatment. The latter demonstrated that the N fertilization reduced BNF by nearly 50% but did not completely inhibit this process. Thus, the zero-N plants counted on three sources of N to satisfy seed N demand: N-BNF, N-soil, and N-fertilizer. Lastly, the high-N treatment also positively impacted yields (+7 bu/a), which could potentially demonstrate a nitrogen limitation toward the end of the SFP for soybeans. Further testing will be performed during the next growing season to provide an improved yield and BNF characterization under different growing seasons (weather).
Keywords: soybean; seed filling period; yield; biological nitrogen fixation